Simultaneous determination of Cd and Pb in antibiotics used in sugar-cane fermentation process by GFAAS - Amorim Filho, Volnei Resta; Polito, Wagner Luiz; de Oliveira, Silvana Ruella; Freschi, Gian Paulo Giovanni; Gomes Neto, José Augusto (Eclética Química, 2006)
A method has been developed for the simultaneous determination of Cd and Pb in antibiotics used in sugar-cane fermentation by GFAAS. The integrated platform of transversely heated graphite atomizer was treated with tungsten to form a coating of tungsten carbide. Six samples of commercial solid antibiotics were analyzed by injecting 20 μL of digested samples into the pretreated graphite platform with co-injection of 5 μL of 1000 mg L -1 Pd as chemical modifier. Samples were mineralized in a closed-vessel microwave-assisted acid-digestion system using nitric acid plus hydrogen peroxide. The pyrolysis and atomization temperatures of the heating program of the atomizer were selected as 600°C and 2200°C, respectively. The calculated characteristic mass for Cd and Pb was 1.6 pg and 42 pg, respectively. Limits of detection (LOD) based on integrated absorbance were 0.02 μg L -1 Cd and 0.7 μg L -1 Pb and the relative standard deviations (n = 10) for Cd and Pb were 5.7% and 8.0%, respectively. The recoveries of Cd and Pb added to the digested samples varied from 91% to 125% (Cd) and 80% to 112% (Pb).